Performance Quality of the State Civil Apparatus of the Sidoarjo Regency Transportation Service: Kualitas Kinerja Aparatur Sipil Negara Dinas Perhubungan Kabupaten Sidoarjo - Pujo, Pujo; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2020)
The State Civil Apparatus (ASN) is a government employee who has a very important role in the implementation of local and regional development. The State Civil Apparatus (ASN) in charge of the Sidoarjo Regency Transportation Service carries out services and maintains an excellent work ethic, as well as the totality of performance so as to provide benefits to the community. The purpose of this research is to describe and analyze the quality of the performance of the State Civil Apparatus at the Transportation Service of Sidoarjo Regency. This study focuses on a performance theory proposed by Mitchell with performance indicators, namely the quality of work. This study uses a descriptive qualitative method with data obtained and collected using observation, documentation, interviews and using books, journals and policy documents as sources. The results of this study are the quality of the performance of the State Civil Apparatus at the Transportation Service of Sidoarjo Regency which has shown good work results in accordance with the rules and tasks given. The existence of providing welfare for the apparatus in the form of rewards for employees whose performance has a positive impact on work motivation. The level of awareness of responsibility in carrying out the duties of each State Civil Apparatus is already high, either with direct or indirect supervision by the leadership.